Responses of Symbiodiniaceae Shuffling and Microbial Community Assembly in Thermally Stressed Acropora hyacinthus - Zhu, Wentao; Liu, Xiangbo; Zhu, Ming; Li, Xinke; Yin, Hongyang; Huang, Jianzhong; Wang, Aimin; Li, Xiubao (Frontiers in Microbiology, 2022)
Although the importance of coral holobionts is widely accepted, the relationship between the flexibility of the microbial structure and the coral host is very complicated. Particularly, the community dynamics of holobionts and the stability of host–microbe interactions under different thermal stresses remain largely unknown. In the present study, we holistically explored the physiology and growth of Acropora hyacinthus in response to increased temperatures (from 26 to 33°C). We observed that bleaching corals with loss of algal symbionts reduced lipids and proteins to maintain their survival, leading to decreased tissue biomass and retarded growth. The diversity of Symbiodiniaceae and symbiont shuffling in the community structure was mainly caused by alterations in the relative abundance of the thermally sensitive but dominant clade C symbionts and low abundance of “background types.” Bacterial diversity showed a decreasing trend with increasing temperature, whereas no significant shifts were observed in the bacterial community structure. This finding might be attributed to the local adjustment of specific microbial community members that did not affect the overall metabolic state of the coral holobiont, and there was no increase in the proportion of sequences identified as typically pathogenic or opportunistic taxa. The Sloan neutral community model showed that neutral processes could explain 42.37–58.43% of bacterial community variation. The Stegen null model analysis indicates that the stochastic processes explain a significantly higher proportion of community assembly than deterministic processes when the temperature was elevated. The weak effect of temperature on the bacterial community structure and assembly might be related to an increase in stochastic dominance. The interaction of bacterial communities exhibits a fluctuating and simplistic trend with increasing temperature. Moreover, temperature increases were sufficient to establish the high stability of bacterial networks, and a non-linear response was found between the complexity and stability of the networks. Our findings collectively provide new insights into successive changes in the scleractinian coral host and holobionts in response to elevated seawater temperatures, especially the contribution of the community assembly process and species coexistence patterns to the maintenance of the coral-associated bacterial community.